Tingkat Culture Shock di Lingkungan Mahasiswa Unsika - Cut Nuraini; Dadang Sunendar; Sumiyadi Sumiyadi (Universitas Indraprasta PGRI Jakarta, 2021)
Culture shock is very much related to the situation where there are worries and uncertainties of excessive feelings and thoughts experienced by people who occupy new and unfamiliar territory. In Unsika Itself, the condition of culture shock is very apparent among students in particular. This condition is not only backgrounded by the status of Unsika which is a State University in the Karawang area, but also because of the position of the City of Karawang which is located on the border of the Capital City known as the center of Metropolitan life. Thus, it more or less affects the social circumstances of the community formed in a state of culture shock. The number of incoming students from various regions and even from the outside of the island, makes the condition of culture shock among the Unsika students varies. However, in this study it was found that the greatest average of the crisis phase was experienced by female students or respondents. Therefore, it is very interesting to be investigated further on the causes and their relevance.